Hybrid cement based on the alkali activation of by-products of coal - F. Rivera, Jhonathan; M. Mejia, Johanna; Mejia de Gutierrez, Ruby; Gordillo, Marisol (Revista de la Construcción. Journal of Construction, 2014)
This study focuses on the production of an alternative cementitious material with low environmental impact through the evaluation of two-coal combustion by-products. Hybrid cements based on the alkali activation of fly ash, (FA) and boiler slag (BS) blend with a proportion of Portland cement (OPC) up to 30% were produced. FA and BS contain an unburned material up to 16%. Response Surface Methodology (RSM) was used to optimize the compressive strength. BS geopolymer achieved high compressive strength (>100 MPa at 28 days) and FA geopolymer reached 30 MPa with thermal curing. The addition of OPC helped modify the curing method. In the case of hybrid based on FA (HFA), there was a significant increase in the compressive strength with levels ranging up to 65 MPa at 28 days without requiring a thermal curing.